Discriminant analysis of physical performance variability in European international Tier 2 rugby union: insights from location-based GPS analysis - Lino-Samaniego, A.; Calleja-González, J.; Martín-Castellanos, A.; Guerrero-Esteban, S.; Roman, I. R.; Solana, D. M. (International Journal of Performance Analysis in Sport, 2025)
This study analysed the physical demands of international Tier 2 rugby union through GPS® technology to extract performance data during official matches of the Rugby European Championship between 2019 and 2022. Besides, the data were used to identify the external load variables that differentiate between home and away games using discriminant analysis. Fifty-five professional male rugby union players from the Spanish national rugby team participated, contributing 210 valid GPS® files through Catapult® Vector S7 GPS® devices recording speed, acceleration, and workload variables. The results revealed that away matches presented higher values in all the statistically significant (p < 0.05) variables such as Total Distance travelled, Total Player Load, Distance per Minute, and effort in relation to specific Speed Bands. The discriminant analysis highlighted 10 metrics that best discriminated between home and away matches, including Player Load per Minute, distance travelled in moderate speed bands, and distance travelled in low- to moderate-intensity Accelerations and Decelerations. The validation of the discriminant model showed a classification accuracy of 72.9%. This study provides relevant information for coaches and physical trainers, allowing them to optimise training strategies and match preparation according to the location. In addition, it highlights the importance and lack of research in Tier 2 international rugby union.